(Re-)conceptualising the international: introduction to the special section. Issue 6 (2nd November 2022) - Çapan, Zeynep Gulsah; Grzybowski, Janis
Abstract: 'The international' is the background condition that holds together inquiries of international politics, orders, systems, societies, practices, and so forth. Albeit being usually taken for granted, its foundational function begs the questions of what the international actually is or, instead, what conceptualisations of the international imply, project, and do. Periodic discussions in International Relations (IR) about the international as the subject matter of the field routinely revolve around attempts to fix its definition, to consciously escape it, or to return to a pragmatic approach of using rather than questioning the concept of the international. In bringing the international from the background to the fore, this Special Section investigates explicit and implicit conceptualisations of the international, and their implications. It does so in a variety of ways and areas. The special section focuses on dynamics of reification and reflection, on how the 'international' is opposed to the 'transnational' or 'the world', how it is denied or seemingly superseded, and how it yet retains its conceptual significance.